2022
DOI: 10.1002/anse.202200068
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Based Biosensors for Imaging of Subcellular Enzymatic Activity

Abstract: As one kind of the most important biomolecules, enzymes participate in nearly all biochemical reactions. Dysregulation of enzymes' spatial distributions and activities is often associated with many diseases. In situ imaging of enzymatic activity at the subcellular level is extremely challenging due to the lack of spatiotemporal precision of sensor probes. In this concept, we introduce several recent works in which DNA-based biosensors with controllable localization ability were constructed for imaging of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…activation. ,, The near-infrared (NIR) light-activated signal amplification strategies have been previously reported for exogenous activation. However, despite exogenously activated tumor-specific imaging has been widely used, there still exist substantial limitations of not being able to tumor site, which currently hinders their clinical applicability. In contrast, endogenous activation offers an alternative approach to achieve tumor-specific imaging with enhanced efficiency. However, due to the complex tumor microenvironment and the instability of catalytic groups, the current endogenous activation-based approaches still have limitations in terms of achieving tumor-specific imaging. ,, Preliminary investigations showed that apurinic/apyrimidinic endonuclease 1 (APE1), a pivotal enzyme that mediates the hydrolysis of apurinic/apyrimidinic (AP) sites, predominantly localizes to the nucleus in normal cells but exhibits enhanced expression in both the cytosolic and nuclear compartments of the cancer cell.…”
Section: Introductionmentioning
confidence: 99%
“…activation. ,, The near-infrared (NIR) light-activated signal amplification strategies have been previously reported for exogenous activation. However, despite exogenously activated tumor-specific imaging has been widely used, there still exist substantial limitations of not being able to tumor site, which currently hinders their clinical applicability. In contrast, endogenous activation offers an alternative approach to achieve tumor-specific imaging with enhanced efficiency. However, due to the complex tumor microenvironment and the instability of catalytic groups, the current endogenous activation-based approaches still have limitations in terms of achieving tumor-specific imaging. ,, Preliminary investigations showed that apurinic/apyrimidinic endonuclease 1 (APE1), a pivotal enzyme that mediates the hydrolysis of apurinic/apyrimidinic (AP) sites, predominantly localizes to the nucleus in normal cells but exhibits enhanced expression in both the cytosolic and nuclear compartments of the cancer cell.…”
Section: Introductionmentioning
confidence: 99%